Socio-demographic and intestinal elimination profile in women treated at a health service (Estima – Brazilian Journal of Enterostomal Therapy, 2020)
Objective: To investigate the profile of intestinal eliminations in women. Method: Cross-sectional study conducted with 41 women seen at a women’s health center in the state of Piauí in Brazil. For data collection, a form was used containing the sociodemographic data and questionnaires that assessed the data on the intestinal elimination pattern with questions based on the Rome IV criteria and the Bristol scale. Results: Of the 41 participants, 56.1% reported consuming one to two servings of fruits or vegetables per day and 51.2% consumed more than two liters of water per day. Regarding the patterns of intestinal elimination, 39% had feces in the Bristol 3 category. As for the Rome IV criteria, 21 (51.2%) women were considered constipated and the frequency of evacuation was statistically significant with the presence of constipation. Conclusion: There was a significant number of women with constipation. There was a need to develop actions that help to cope with the problem and improve the quality of life of this population.